AGRO Climatic Regional Planning at District and Sub-District Level (Executive Summaries of 10 Districts) - Planning Commission (Planning Commission, 1992)
District Planning can be seen as a part of multi-level planning involving rational assessment of resource endowment, appropriate technology and needs at local level. Planning for development activities at this level has to incorporate, on the one hand linkages with the higher order spatial unit (State) and, on the other, reflect the problems and priorities at the lower level i.e. block and village.
Agro Climatic Regional Planning Unit Planning Commission
Agro Climatic Regional Planning Unit Planning Commission